An enhanced treatment efficiency for diluted palm oil mill effluent using a photo-electro-Fenton hybrid system - Noralisya, Ali; Chee, Beng Yoh; Lau, Seng; Tay, Meng Guan (The Journal of the Serbian Chemical Society, 2018)
Photocatalysis, electrolysis and Fenton process are three important advanced oxidation processes (AOPs) which produces hydroxyl radical to degrade organic matter in wastewater within 4-6 hours under ambient conditions. A photocatalysis, electrolysis and Fenton (photo-electro-Fenton) process hybrid system has been carried out to treat diluted palm oil mill effluent (POME) in this study. An electrolytic cell was set up with a stainless steel anode and a platinum wire cathode with applied cell potential of 3V. Diluted POME was then treated in the cell with the mixture of titanium oxide (TiO2) as the photocatalyst, sodium sulfate (Na2SO4) solution as the electrolyte, hydrogen peroxide (H2O2) and iron sulfate (FeSO4) as the Fenton reagents. The effects on the duration, pH, concentration of TiO2 and different light conditions on the removal efficiency of chemical oxygen demand (COD) of the diluted POME were studied. The optimal conditions for the photo-electro-Fenton hybrid system were found to be 4 hr contact time at pH 4 with 60 mg/L TiO2 under sunlight. With such conditions, the COD removal efficiency was able to achieve 97 %. On the other hand, the photo-electroFenton hybrid system gave the highest COD removal efficiency compared to the electro-Fenton hybrid system, Fenton and photocatalyst, respectively.